Corruption Criminal Accountability in the Management of Village Owned Business Entities (BUM Desa) : (Conceptual Study of the Abuse of Village Financial Management Authority) - I Putu Kisnu Gupta; Rosidah Husniyah; Putu Eka Wisniawati (Journal of Development Research, 2023)
The development of the spirit of regional autonomy is characterized by the enactment of Law Number 22 of 1999 concerning Regional Government, which encourages Villages to establish a business entity that aligns with the needs of the local community. This business entity is commonly referred to as Village-Owned Enterprises (BUM Desa). Village-Owned Enterprises are used to manage a business, utilize assets, develop investment and productivity, provide services and/or provide other types of businesses. With its status as a legal entity, the role of Village Owned Enterprises is increasingly important as a consolidator of community products/services, producers of various community needs, incubator of community businesses, providers of public services and various other functions. The development of Village-Owned Enterprises which have their own wealth originating from APBN and/or APBD funds is inseparable from the poor management carried out by Village-Owned Enterprises who abuse the authority they have. Furthermore, this abuse of authority can have implications for criminal acts of corruption in the management of village-owned enterprises, which can be held accountable for criminal corruption for perpetrators. This study uses normative research methods. The result of this research is that it is necessary to assert in the legislation that regulates the mechanism of settlement and accountability of Village-Owned Enterprises (BUM Desa) for errors and/or negligence in the management of BUM Desa.